Evaluation of Blood Alcohol Concentrations after Oral Administration of a Fixed Combination of Thyme Herb and Primrose Root Fluid Extract to Children with Acute Bronchitis - Ludwig, S.; Stier, H.; Weykam, S. (Drug Research, 2016)
Background: The application of alcohol-containing medicinal products to children has been a subject of discussion for many years. A safety threshold of 0.125‰ blood alcohol concentration following the administration of a single dose has been recommended by the European Medicines Agency.The aim of this clinical study was to prove the safety of administering a fixed combination of thyme herb and primrose root fluid extract (Bronchicum® Elixir) containing 4.9% ethanol.Methods: The herbal drug was administered for a period of 7–9 days to 16 children (ages 1–12 years) suffering from acute bronchitis for≤48 h. After 3–5 days, a blood sample was taken 45 min (children≥5 years: also 0 and 90 min) after application of the drug. The efficacy was assessed using the Bronchitis Severity Score. Global efficacy and tolerability were rated by the investigator and patients.Results: All measured blood ethanol concentrations were below the threshold (mean value after 45 min: 0.0029±0.0057‰ and after 90 min: 0.0051±0.0078‰). The Bronchitis Severity Score decreased from 6.6±1.0 to 0.9±1.6 points. Global efficacy was assessed as “very good” and “good” in 60% (investigator) and 80% (patients) of cases. Global tolerability was rated as “very good” and “good” in more than 90% of cases.Conclusion: In conclusion, oral administration of the drug containing 4.9% ethanol to children (age 1–12 years) demonstrated a favourable risk/benefit ratio of the drug.
Keywords: herbal medicinal product; ethanol; safety; threshold; clinical study; paediatric